Solenergi - Douhan, Johan; Rejstrand, Henrik (2007)
A possible way to reduce pollution and slow down the process of global warming is to increase the usage of renewable energy sources. One of these renewable energy sources is solar power. With the aid of solar panels and solar cells the energy from the sun can be transformed into both heating and electricity. The requirement to use the sun in this fashion is a suitable surface, for example a big roof, an angle between 40-60 degrees and that the surface should be exposed to the south. Almost every farm meets these requirements.